Apoyo social percibido en adultos con experiencia de embarazo en la adolescencia: un estudio retrospectivo en cuatro ciudades colombianas (2021)
The objective of the study was to find out the perception of social support that adults who have a teenage pregnancy experience currently have. The participants were 305 adults, men and women with experience of teenage pregnancy, 22% born in Bogotá, 27.9% in Montería, 31.5% in Ibagué and 18.7% in Pereira. With ages between 20 and 56 years, 129 men (42.3%) and 176 women (57.7%), the selection of the sample was not probabilistic, but through personal and institutional contacts in each of the 4 cities. The researchers traveled to the cities indicated above and carried out the collection of information in each one of them using a survey prepared for this purpose (see Annex 1. The results showed that the support received from the families was the most frequent and valued. as satisfactory by men and women This implies that the extended family, the grandparents, the siblings, supported the young people to get ahead from the emotional and material point of view mainly. In the case of Colombian society, there seems to be a greater strength of the family in general to provide support, than the state. Regarding the community, the region that showed the highest perception of social support was Montería. On the other hand, the perception of state support was perceived as scarce, with the exception of the city In conclusion, it can be determined that the family socializes from children to people to become mothers or fathers as part of their ro l of gender and their life objective and it is they who are in charge of supporting them during pregnancy and afterwards. . The state in this study seems blurred as a source of support and the community also lacked the strength to support. Among the conclusions, extended families emerge as an important element in any plan for the prevention of adolescent pregnancy. Families become the important focus of intervention, even more than adolescents, to prevent pregnancies at these ages.Keywords: adolescent pregnancy, perception of social support, state, community,family, ecosystem model.